The Influence of Organizational Experience on Career Maturity - Dewi Sukmawati (Universitas Muhammadiyah Malang, 2022)
The background of this research was that there waas tendency about on the need of organizational experience to increase the maturity of the student's career. This research aims to know the influence of organization experience toward the career maturity (study at University of Muhammadiyah Malang). This type of research is an explanatory research which is included in the quantitative method with a questionnaire for data collection. The sampling technique used was accidental sampling technique. Data analysis used was using Path Analysis and used the SmartPLS 3.0 program. These results of this study indicate that organization experience has a significant positive effect on the career maturity.